2016
DOI: 10.1093/mnras/stw1069
|View full text |Cite
|
Sign up to set email alerts
|

The clustering evolution of dusty star-forming galaxies

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 120 publications
4
31
0
Order By: Relevance
“…The separation disappears at > z 3, as discussed in Section 5.2 this could be due to the increasing contamination of dusty galaxies on the UVJ-selected quiescent populations. The latest model predictions by Cowley et al (2016) on the clustering of both faint and bright SMGs are systematically lower in all three redshift bins.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The separation disappears at > z 3, as discussed in Section 5.2 this could be due to the increasing contamination of dusty galaxies on the UVJ-selected quiescent populations. The latest model predictions by Cowley et al (2016) on the clustering of both faint and bright SMGs are systematically lower in all three redshift bins.…”
Section: Discussionmentioning
confidence: 74%
“…The dotted curves show the autocorrelation functions of dark matter. We also show in green dashed curves the latest predictions based on the semi-analytic model GALFORM (Cowley et al 2016). At < z 3, the comparison quiescent galaxies have systematically higher clustering amplitude, whereas TCGs and comparison starforming galaxies are similarly clustered in all redshift bins.…”
Section: Two Point Autocorrelation Function and Large-scale Power-lawmentioning
confidence: 73%
“…However, when galaxies are selected by their star formation rates, N cen does not necessarily reach unity (e.g. Zheng et al 2005;Contreras et al 2015;Cowley et al 2016). This implies that haloes above a certain mass will not necessarily harbour a star forming galaxy or, in our case, an ELG.…”
Section: The Mean Halo Occupation Distributionmentioning
confidence: 99%
“…Predicted evolution of large-scale bias with redshift. Green squares with errorbars represent the bias measured directly from the 3D spatial correlation function of SMGs with S 850µm > 4 mJy, as is done in Cowley et al (2016). The 1σ errors are calculated using the volume bootstrap method advocated in Norberg et al (2009).…”
Section: A Cross-correlation Analysis Of Sub-mm Sourcesmentioning
confidence: 99%
“…Fakhouri et al 2010), which can then be compared to the halo masses inferred from the observed clustering of local galaxy populations. However, the spread in the host halo masses of SMG descendants could be significant (∼ 2 dex, Cowley et al 2016) due to the hierarchical growth of structure.…”
Section: Introductionmentioning
confidence: 99%